USP5-Mediated PD-L1 deubiquitination regulates immunotherapy efficacy in melanoma - Jiaheng Xie; Pengpeng Zhang; Yuankun Liu; Dan Wu; Xueqi Ou; Ming Wang; Wei Yan; Jianlan Liu; Jian Tang; Tianyi Ni; Chenfeng Ma; Qikai Tang; et al. (Journal of Translational Medicine)
Abstract Background The role of post-translational modifications(PTMs) in PD-L1-mediated immune resistance and melanoma progression remains poorly understood. Methods We conducted multi-omics analyses and constructed a prognostic model based on PTM-related genes using machine learning to identify key regulators in melanoma. In vitro and in vivo experiments, including cell culture, flow cytometry, and subcutaneous allografts models, were used to investigate USP5’s function. Protein-protein interactions were validated using Western blotting and co-immunoprecipitation, while PD-L1 stability and ubiquitination were assessed using cycloheximide (CHX) chase and ubiquitination assays. Results USP5 was identified as a key DUB that specifically deubiquitinates K48-linked polyubiquitin chains on PD-L1, stabilizing its protein levels. USP5 knockdown reduced PD-L1 expression, enhanced CD8 + T-cell infiltration and activation, and suppressed melanoma progression in both in vitro and in vivo models. Furthermore, combining USP5 knockdown with anti-PD-1 therapy significantly improved therapeutic efficacy by reducing tumor burden and promoting T-cell activation. Conclusion USP5 promotes immune escape in melanoma by stabilizing PD-L1 through deubiquitination, representing a novel mechanism hindering the efficacy of ICIs. Targeting USP5 could enhance anti-PD-1 therapy and improve patient outcomes. These findings underscore the therapeutic potential of USP5 inhibition as a strategy to overcome immune resistance in melanoma.